El Excentrico, 1978-05-20 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
May 20, 1978 [20 de mayo de 1978]. Ano 29, No 4. Cover contains a group photo of Community Leader Carlos Gomez, Mayor Janet Gray Hayes, Biblioteca Latina Board President Jose Angulo, and UAW Member Willie Regalado. This cover also serves a political advertisement to re-elect Hayes as mayor.